Docking Study of Naphthalene Compounds from Eleutherine Bulbosa as Antidiabetic Agents on Multiple Receptors - Anam, Syariful; Yuyun, Yonelian; Yusriadi, Yusriadi; Sultan, Asriana; Pakaya, David; Maulana, Saipul; Zubair, Muhammad Sulaiman (Molekul, 2025)
ABSTRACT. Diabetes Mellitus is a severe disease to the world health community; it is estimated that 700 million people worldwide will suffer from it. The approach taken to this disease includes improving lifestyle and pharmacological therapy. Recent pharmacological therapeutic approaches include inhibiting the α-glucosidase enzyme, the dipeptidyl peptidase 4 (DPP-4) enzyme, and the sodium-glucose co-transporter-2 (SGLT-2) protein. This research aims to conduct a docking study on three naphthalene compounds from Eleutherine bulbosa against three receptors: α-glucosidase, the DPP-4, and the SGLT-2 protein. The methods used are protein structure preparation, docking protocol validation, preparation of E. bulbosa test ligand structures, and molecule docking for test compounds. Validation was carried out by calculating the Root Mean Square Deviation (RMSD) values using PyMOL software; the results showed that the RMSD value of native ligands was <2Å. Molecular docking of the test compounds was conducted using Autodock Vina 1.2.3 ver 2020. Eleutherinoside A showed the highest binding against the α-glucosidase and DPP-4 protein. Eleuthoside B has the most increased binding to SGLT-2 protein. The research concluded that three naphthalene compounds from E. bulbosa can be used as an antidiabetic agent. Keywords: Antidiabetic; Docking study; Eleutherine bulbosa; Naphthalene; α-glucosidase; DPP-4; SGLT-2